Assessing Nutritional Knowledge, Attitudes and Practices and Body Mass Index of Adolescent Residents of Orphanage Institutions in Selangor and Malacca - Shaziman, Syimir bin; Mohd Rani, Mohd Dzulkhairi; Nor Aripin, Khairun Nain bin; Abdul Hamid, Nazefah; Sulaiman, Wan Noraini Wan; Rahman, Zairina A.; Abdullah, Mohd Yunus (Pakistan Journal of Nutrition, 2017)
Background and Objective: Orphaned children face an increased risk of being malnourished. This study was aimed to explore knowledge and attitudes towards nutrition as well as nutritional practices and Body Mass Index (BMI) of adolescent residents of orphanages. Methodology: Five orphanage institutions in Selangor and Malacca were chosen for this study and 85 adolescents aged 13-18 years old were enrolled. Questionnaires concerning nutritional knowledge were administered in face-to-face interviews to prevent bias and to ensure questionnaire completion. Results: The results showed that out of the 85 subjects, 80% were orphans and 20% non-orphans. The majority of respondents were of normal weight (61.2%), while 2.4 and 4.7% were thin and severely thin, respectively. Meanwhile, 16.5% of subjects were overweight and 15.3% were obese. Fewer than 20% of respondents (14/85) were scored as having a “good” level of nutritional knowledge score but more than half had nutrition attitude and practice scores within the “good” range. Although no significant correlation was found between nutrition knowledge and attitude (rp = -0.043, p = 0.694) or knowledge and practice (rp = -0.222, p = 0.148), there was significant correlation between nutrition attitude and practice (rp=0.295, p = 0.006). Conclusion: Less than half of the total respondents obtained a “good” score for nutritional knowledge but the majority of the participants scored at the “good” level for attitude and practice. Although most respondents scored at the “good” level for nutritional practice, this outcome was not reflective of the situation as a whole, particularly given the “poor” scores for exercise and breakfast practices.